(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper examines the interaction of socialist ideas and doctrines over the last three decades with the development of Indian economic policy. It concludes with an analysis of the differences in relation to these socialist objectives between ex-unte aspirations and ex-post outcomes.